Association of suicidal thoughts to deployment: Preliminary findings when considering time since return and combat exposure. (2nd April 2020) - Griffith, James
Abstract: Since 2002, the U.S. military has seen a dramatic rise in suicides. Risk was thought to be associated with having been deployed, although little or no association has been found. This association may be obscured by the omission of important aspects of deployment, such as time since return from deployment and combat exposure. Survey data obtained from Army National Guard soldiers who had been deployed to Iraq during 2010 were examined ( N = 4567 soldiers in 50 company-sized units). Overall, the relationship of suicidal thoughts to time since having returned was not statistically significant. However, among soldiers who reported more than one combat event, twice as many soldiers who had returned over a year ago reported suicidal thoughts than soldiers who returned 1 year or under. In addition, about twice as many soldiers who had participated in a traumatic combat event or in direct combat reported suicidal thoughts after having returned over 1 year than soldiers who returned more recently. Findings are discussed relative to future studies of suicide risk among reserve personnel, especially, a year or more since having returned.